1999
DOI: 10.1073/pnas.96.26.14681
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of HIV-1 from follicular dendritic cells during HAART: Mathematical analysis

Abstract: The pool of HIV type 1 (HIV-1) on follicular dendritic cells (FDC) is an important reservoir that has the potential to perpetuate infection (1-3). Although antiretroviral therapies that block viral replication have no direct effect on viral clearance, these therapies are associated with loss of HIV-1 from FDC (4-7). Cavert et al. (4) observed that the amount of HIV-1 on FDC, estimated as Ϸ10 11 virions, decreased by up to 5-fold during the first 2 d of potent antiretroviral therapy and by up to more than four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 43 publications
(37 reference statements)
2
74
1
Order By: Relevance
“…At low densities (as in our mice), many FDC Fc and complement receptors should be available, and trapped HIV immune complexes could be anchored to FDCs in more stable, highly multivalent states of attachment. This postulate is consistent with mathematical modeling of HIV-1 dissociation from FDCs (37), as well as a model of the kinetics of viral decline in patients on HAART (38). Importantly, it has been reported that even under HAART, some HIV replication continues (10, 28 -30, 39), and we reason that this FIGURE 5.…”
Section: Figuresupporting
confidence: 68%
See 1 more Smart Citation
“…At low densities (as in our mice), many FDC Fc and complement receptors should be available, and trapped HIV immune complexes could be anchored to FDCs in more stable, highly multivalent states of attachment. This postulate is consistent with mathematical modeling of HIV-1 dissociation from FDCs (37), as well as a model of the kinetics of viral decline in patients on HAART (38). Importantly, it has been reported that even under HAART, some HIV replication continues (10, 28 -30, 39), and we reason that this FIGURE 5.…”
Section: Figuresupporting
confidence: 68%
“…These data are in apparent contradiction to the longer decay periods observed in our murine study, although Hlavacek et al (37), using a stochastic model of decay, calculated that with a beginning virus load of 10 11 copies of RNA, virions could still be expected for as long as 10 yr. We hypothesize that differences between the Cavert study and ours may be related to analysis of the FDC network under very different conditions of FDC-virus density. At high virus densities (as would occur in untreated subjects), limited numbers of FDC Fc and complement receptors may be available for binding viral immune complexes, resulting in many less stable, univalent interactions.…”
Section: Figurecontrasting
confidence: 54%
“…1) (20). The model omits other processes that might influence the decay of FDC-associated virus, such as turnover of FDCs, internalization of HIV-1, shedding of HIV-1 on iccosomes (22), stripping of HIV-1 by cells that interact with FDCs, structural breakdown of virions, and recovery of the FDC network during therapy (13).…”
Section: Modelmentioning
confidence: 99%
“…We consider measurements of plasma viral load (14), FDC-associated HIV-1 RNA (5), infected mononuclear cells in LT (5), and CD4 ϩ T cells in LT (12) during treatment for eight patients. The model combines earlier models for HIV-1 dynamics (19) with a recent model for the reversible binding of HIV-1 to FDCs (20). Fig.…”
mentioning
confidence: 99%
“…Infected macrophages and virus trapped on the follicular dendritic network (FDC) of lymphoid tissues are secondary sources (1)(2)(3). These virus sources might be eradicated with a few years of treatment (3,4), although the long-term clearance kinetics of FDC-associated virus is unknown (5,6). Stable, latently infected cells, harboring replication competent virus have been found to persist after many years of suppression of viremia to Ͻ50 copies per ml (7)(8)(9).…”
mentioning
confidence: 99%